Future English Teachers’ Perspective towards the Implementation of E-Learning in Covid-19 Pandemic Era - Reza Pustika (Yayasan Visi Intan Permata, 2020)
This research was conducted to investigate the future English teachers’ perspective towards the implementation of e-learning in Covid-19 pandemic era. There were 60 respondents involved in this research. A survey method was carried out in this research. The data of this research was collected by distributing a questionnaire. The questionnaire was formulated based on the theories about the pros and cons of the e-learning implementation. Descriptive analysis was done to analyzed this research data. The data of this research was transformed into percentage. The result of this research showed that the future English teachers find e-learning is beneficial for them, but still have some lacks to overcome. Besides, the subjects of this research are aware of things they need to prepare before they conduct e-learning, and they also suggest the stakeholders in Indonesia to improve the technology development to support the e-learning implementation.